The frequent traveler's guide - Anolik, Alexander (Sphinx Pub., 2005)
You know how frustrating it is when something goes wrong on a trip. You also know how unsettling it can be when you do not get the satisfaction you deserve. The Frequent Traveler's Guide can take these worries away. Written by travel industry experts, this guide gives you the confidence to not only know your rights, but to excercise them and get the results you want. Whether you are taking that once in a lifetime vacation or flying home from your third business trip this week, here is information you can use.